Progressive Hemifacial Atrophy and Linear Scleroderma En Coup de Sabre: A Spectrum of the Same Disease? - Khamaganova, Irina (Frontiers in Medicine, 2018)
Similar clinical and histhopathological features in progressive hemifacial atrophy and linear scleroderma en coup de sabre are well known. Trauma may predispose to the development of both diseases. The lack of association with anti- Borrelia antibodies was shown in both cases as well. The otolaryngological and endocrine disorders may be associated findings in both diseases. However, there are certain differences in neurological and ophthalmological changes in the diseases.